Motivation and Engagement in Teaching Learning Process at Basic Level in Nepal - Adhikari, Toyanath (Pragya Darshan प्रज्ञा दर्शन, 2025)
This research article, Motivation and Engagement in Teaching Learning Process at Basic Level in Nepal aims to examine how motivation and engagement influence the learning experience. The study's objective is to uncover the ways in which these two factors contribute to students' learning. The article employs a qualitative research design, utilizing methods like open-ended questions, teacher interviews, and literature reviews to gather data. The goal is to identify effective strategies to enhance student engagement and motivation. Ultimately, the study aims to deepen the understanding of the significance of engagement and motivation within the broader educational process, offering practical recommendations for educational practice and policy. Teachers' opinions vary, with some believing both factors (motivation and engagement) are equally crucial, while others prioritize engagement over motivation or vice versa. The key finding is that both engagement and motivation are vital in the learning process, though their influence differs depending on the educational context.